Bird species present in urban parks are more colorful than urban avoiders: A test in the Argentinian Pampas - Lucas M. Leveau (Avian Research)
Bird plumage color has been assessed as a possible trait driving the presence of bird species in urban areas. Although some species can see the ultraviolet (UV) spectrum, the mentioned studies did not take into account UV reflectance when characterizing bird plumage. This study aimed to use a recent database of the colorfulness in passerines that incorporated the UV spectrum to compare bird colorfulness and other traits between urban parks and rural areas in Central-East Argentina. Birds in urban parks were surveyed in 51 parks in 6 cities during breeding and non-breeding seasons. A list of Passeriformes species from parks was created, and a list of urban avoider species was created from the bibliography. Species traits were body mass, clutch size, migratory status, nesting site, diet and habitat breadth, and plumage colorfulness. A total of 85 species were detected in the regional pool, of which 30 species were detected in urban parks. Bird species present in urban parks were more colorful than bird species only present in rural areas. In addition, bird presence in urban parks was positively related to their regional frequency and diet breadth. Moreover, urban presence was related to nesting on trees and buildings, whereas species not present in urban parks nested on the ground. The results obtained showed that bird color is significantly associated with presence of bird species in urban parks.